BpOmpW Antigen Stimulates the Necessary Protective T-Cell Responses Against Melioidosis - Tomás-Cortázar, Julen; Bossi, Lorenzo; Quinn, Conor; Reynolds, Catherine J.; Butler, David K.; Corcoran, Niamh; Murchú, Maitiú Ó; McMahon, Eve; Singh, Mahavir; Rongkard, Patpong; Anguita, Juan; Blanco, Alfonso; et al. (Frontiers in Immunology, 2021)
Melioidosis is a potentially fatal bacterial disease caused by Burkholderia pseudomallei and estimated to cause 89,000 deaths per year in endemic areas of Southeast Asia and Northern Australia. People with diabetes mellitus are most at risk from melioidosis, with a 12-fold increased susceptibility for severe disease. IFN- responses from CD4 and CD8 T cells, but also from NK and NKT cells are necessary to eliminate the pathogen. We previously reported that immunisation with BpOmpW protected mice from lethal B. pseudomallei challenge for up to 81 days. Elucidating the immune correlates of protection of the protective BpOmpW vaccine is an essential step prior to clinical trials. Thus, we immunized either non-insulin resistant C57BL/6J mice or an insulin resistant C57BL/6j mouse model of Type 2 Diabetes (T2D) with single dose of BpOmpW. BpOmpW induced strong antibody responses, stimulated effector CD4+ and CD8+ T cells and CD4+ CD25+ Foxp3+regulatory T cells and produced higher IFN- responses in CD4+, CD8+, NK and NKT cells in non-insulin resistant mice. The T cell responses of insulin resistant mice to BpOmpW were comparable to those of non-insulin resistant mice. In addition, as a precursor to its evaluation in human studies, humanised HLA-DR and HLA-DQ transgenic mice elicited IFN- recall responses in an ELISPoT-based study. Moreover, human donor PBMCs exposed to BpOmpW for seven days showed T cell proliferation. Finally, plasma from melioidosis survivors with diabetes recognized our BpOmpW vaccine antigen. Overall, these range of approaches used strongly indicate that BpOmpW elicits the necessary immune responses to combat melioidosis and bring the vaccine closer to clinical trials.